Application of water hyacinth (Eichhornia crassipes) for phytoremediation of ammoniacal nitrogen: A review - Ting, W. H.T.; Tan, I. A.W.; Salleh, Shanti Faridah; Wahab, N. A. (Elsevier Ltd, 2018)
Water eutrophication is a serious global issue that needs urgent attention. Ammoniacal nitrogen (AN) is present in both domestic and industrial wastewater which acts as one of the main contributors of eutrophication. There is a need to reduce AN to permissible levels as enforced by local authorities before final discharge. Phytoremediation has been recommended as an alternative solution to other conventional physiochemical and biological methods to treat wastewater with high AN content due to its cost-effective, environmental friendly and sustainable characteristics. Water hyacinth (Eichhornia crassipes) is a free-floating macrophyte, which is known as the most noxious weed in the world that shows characteristics of fast growth rate, adaptability to a wide range of environmental conditions and high nutrient uptake capacity. These capabilities contribute to the wide applications of water hyacinth for phytoremediation purpose. This paper provides extensive review on the technical advantages and limitations of phytoremediation as compared to other nitrogen removal technologies, as well as the insight for the development of phytoremediation technology using water hyacinth to treat wastewater with high AN content. This paper also provides fundamental knowledge on the AN removal mechanisms and necessary considerations in selecting the operating conditions of water hyacinth-based phytoremediation system, which may facilitate the design of industrial scale phytoremediation system for effluent treatment. Overall, phytoremediation technology assisted by water hyacinth has been shown to be promising for AN removal, which can be a potential solution in the future for various industries to reduce the AN level in their effluent discharge. © 2018 Elsevier Ltd